Effects of naringenin on lipogenesis, lipolysis and glucose uptake in rat adipocyte primary culture: a natural antidiabetic agent - Lim, S.L.; Soh, K.P.; Kuppusamy, U.R. (2008)
The flavonoid naringenin is commonly found in citrus fruits and tomato. The main aim of this study was to assess the in vitro insulin-like effects of naringenin using rat adipocyte primary culture. The adipogenic, lipolytic and glucose uptake activities of naringenin in primary rat adipocytes were assessed using Oil Red O, glycerol, and 2-deoxy-D-2,6-3Hglucose uptake quantitative assays respectively. Naringenin exhibited significant increase of lipogenesis in the presence and absence of insulin in primary rat preadipocytes. At the concentration range of 0.01 - 100 ÂµM, naringenin inhibited 50 % of epinephrine induced lipolysis in rat adipocytes and enhanced insulin's antilipolytic activity. Naringenin (100 ÂµM) stimulated 163 % glucose uptake in rat adipocytes (compared to untreated cells) and this was significantly higher than the insulin mediated glucose uptake at similar concentration. Thus, naringenin may play an important role as an adjuvant and/or alternative to insulin therapy for the management of diabetes mellitus. ABSTRACT FROM AUTHOR Copyright of Internet Journal of Alternative Medicine is the property of Internet Scientific Publications LLC and its content may not be copied or emailed to multiple sites or posted to a listserv without the copyright holder's express written permission. However, users may print, download, or email articles for individual use. This abstract may be abridged. No warranty is given about the accuracy of the copy. Users should refer to the original published version of the material for the full abstract. (Copyright applies to all Abstracts.)